2000
DOI: 10.1021/jm000129j
|View full text |Cite
|
Sign up to set email alerts
|

Topoisomerase I-Mediated Antiproliferative Activity of Enantiomerically Pure Fluorinated Homocamptothecins

Abstract: Homocamptothecin (hCPT) is an E-ring modified camptothecin (CPT) analogue bearing a methylene spacer between the alcohol and carboxyl functions of the CPT lactone. Combining pronounced inhibitory activity of topoisomerase I (Topo I) with enhanced plasma stability, hCPT constitutes an attractive template for the elaboration of new anticancer agents. Fluorinated hCPT analogues, prepared in enantiomerically pure form, were assayed by their stimulation of Topo I-mediated DNA cleavage. Translation into cytotoxicity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
27
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 70 publications
(28 citation statements)
references
References 15 publications
1
27
0
Order By: Relevance
“…Although Pgp is not implicated in resistance to hCPTs (Lavergne et al, 2000a;Larsen et al, 2001), hCPTs have been shown to be subject to transport by MRP1 (Chauvier et al, 2002) and ABCG2 . In addition, selection with CPTs usually results in overexpression of ABCG2 (Maliepaard et al, 1999;Kawabata et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Although Pgp is not implicated in resistance to hCPTs (Lavergne et al, 2000a;Larsen et al, 2001), hCPTs have been shown to be subject to transport by MRP1 (Chauvier et al, 2002) and ABCG2 . In addition, selection with CPTs usually results in overexpression of ABCG2 (Maliepaard et al, 1999;Kawabata et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…This modification decreases the rates of hydrolysis and conversion to the carboxylate and also prevents the reverse reaction, i.e., the conversion of the homocamptothecin carboxylate to lactone (Lavergne et al, 1998;Lesueur-Ginot et al, 1999). Interestingly, homocamptothecins are more potent Top1 inhibitors than camptothecins and retain potent antitumor activity (Lavergne et al, 1998(Lavergne et al, , 2000Bailly et al, 1999;Lansiaux et al, 2001;Larsen et al, 2001). A difluoro homocamptothecin derivative, difluoro-camptothecin (BN80915), whose Top1 and antitumor activity in model systems are greater than those of homocamptothecin (Lansiaux et al, 2001;Larsen et al, 2001), is being pursued for clinical development.…”
mentioning
confidence: 99%
“…The compound acts as a potent Topo I poison as expected for both CPT and hCPT analogs (12,29,30). BN80927 performs well in isolated enzyme assays but also on living cells.…”
Section: Discussionmentioning
confidence: 89%